2016
DOI: 10.53761/1.13.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The feedback process: Perspectives of first and second year undergraduate students in the disciplines of education, health science and nursing

Abstract: The purpose of this study was to determine the current perspectives of feedback from first and second year undergraduate students enrolled in blended units of study which incorporated both face-to-face and online components. Students enrolled in a unit of study taught by the School of Health Sciences at the University of Tasmania were surveyed to broadly determine their perception of the feedback process. Responses from the 55% of the cohort who completed the survey indicated that students recognised a wide va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Feedback is a vital and vigorous element in education 6 . It refers to helpful information in the form of appreciation or denunciation to an individual.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback is a vital and vigorous element in education 6 . It refers to helpful information in the form of appreciation or denunciation to an individual.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback is information or data from another person specific to an assignment or skill performance that may include validation or explain gaps in performance (Douglas et al, 2016;Kamiya, 2018). Feedback should be timely, clear, easy to understand, and purposeful in supporting improvement and development (Leibold & Schwarz, 2015).…”
Section: Background Of Online Feedbackmentioning
confidence: 99%
“…Researchers should also describe the data synthesis related to the purpose (Hong & Pluye, 2019). The researchers combined the seven levels of On the contrary, Douglas et al (2016) found that 50% of students perceived less timely feedback, while 20% perceived that feedback was timely. Further, the timeliness of the feedback was a factor in their perception of a negative or positive feedback experience.…”
Section: Study Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…For feedback to be most effective, assessment and feedback need to be coherently integrated into the overall course context (Gibbs and Simpson 2004), with certain approaches to feedback being more effective for certain assignments-for example, as Jonsson notes, "if the students are engaged in one particular assignment, which is to be revised, they want more corrective feedback so that they can make improvements for the final version" (Jonsson 2012, p. 67; see also Glover & Brown 2006). As well, students need illustration and guidance in order to make productive use of feedback (Agius & Wilkinson 2014;Bailey 2009;Doan 2013;Douglas et al 2016;Pokorny & Pickford 2010;Robinson et al, 2013;Winstone et al 2017), particularly in early years (Pokorny & Pickford 2010;Robinson et al (2009, p. 12). Orsmond and Merry, speaking specifically of Biology students, bring out the importance of ensuring that students understand the basis for the feedback, so as to ensure that they are not working in "a disempowered way" (2011, p. 133).…”
Section: Introductionmentioning
confidence: 99%